The ways of solving the problems of environmental safety forces in peace-making operations - Петрухін, Сергій Юрійович; Артем’єв, Сергій Робленович; Пісня, Леонід Андрійович (Eastern-European Journal of Enterprise Technologies, 2012)
The ways of the development of corporative ecological-informational system on the basis of the functional and structural approach are considered. The implementation of the ecological profile of the MNTG in the peace-making operations when solving the tasks of the troops ecological safety and effective management of the environment status is offered